Teori dan Metode Otentisitas Hadis - Handayani, BQ. Citra; Hidayati, Nurul; Zaki, Mohamad (TAMADDUN: Jurnal Ilmu Sosial, Seni, dan Humaniora, 2023)
This paper explores the authenticity of hadith, a key area of study in ‘ulūm al-ḥadīth, with a focus on the development of the sanad (chain of transmission). Sanad emerged after the death of Prophet Muhammad (peace be upon him), and while methods varied during the era of the Companions, it reached its peak by the end of the first century. The study of hadith transmission has drawn interest from both Muslim scholars and non-Muslim researchers, such as Schacht, whose “Projecting Back” theory is considered difficult to implement. Three main perspectives on hadith authenticity have emerged: a skeptical view by Mahmud Abu Rayyah, a non-skeptical view by Yusuf al-Qaradawi, and a middle-ground approach by Muhammad al-Ghazālī. This qualitative study, using library research, examines classical and modern authentication methods, concluding that both are necessary for assessing hadith authenticity.